Rising tide the great Mississippi flood of 1927 and how it changed America - Barry, John M. (Simon & Schuster, 1997)
Rising Tide begins in the nineteenth century, when the first serious attempts to control the river began. The story focuses on engineers James Eads and Andrew Humphreys, who hated each other. Out of the collision of their personalities and their theories came a compromise river policy that would lead to the disaster of the 1927 flood yet would also allow the cultivation of the Yazoo-Mississippi Delta and create wealth and aristocracy, as well as a whole culture. In the end, the flood had indeed changed the face of America, leading to the most comprehensive legislation the government had ever enacted, touching the entire Mississippi valley from Pennsylvania to Montana. In its aftermath was laid the foundation for the New Deal of Franklin D. Roosevelt
Keywords: Eads, James Buchanan <1820-1887>; Humphreys, A. A <1810-1883> -- (Andrew Atkinson); Percy family; Geschichte 1900-2000; Geschichte 1927; Gevolgen; Mississippi (rivier); Overstromingen; Politieke aspecten; Geschichte; Politik; Flood control -- Mississippi River -- History; Floods -- Mississippi River Valley -- History -- 20th century; Überschwemmung; Mississippi River Valley -- History -- 1865-; Mississippi -- Fluss